FlhF Is Required for Swarming Motility and Full Pathogenicity of Bacillus cereus - Mazzantini, Diletta; Celandroni, Francesco; Salvetti, Sara; Gueye, Sokhna A.; Lupetti, Antonella; Senesi, Sonia; Ghelardi, Emilia (Frontiers in Microbiology, 2016)
Besides sporulation, Bacillus cereus can undergo a differentiation process in which short swimmer cells become elongated and hyperflagellated swarmer cells that favor migration of the bacterial community on a surface. The functionally enigmatic flagellar protein FlhF, which is the third paralog of the signal recognition particle (SRP) GTPases Ffh and FtsY, is required for swarming in many bacteria. Previous data showed that FlhF is involved in the control of the number and positioning of flagella in B. cereus. In this study, in silico analysis of B. cereus FlhF revealed that this protein presents conserved domains that are typical of SRPs in many organisms and a peculiar N-terminal basic domain. By proteomic analysis, a significant effect of FlhF depletion on the amount of secreted proteins was found with some proteins increased (e.g. B component of the non-hemolytic enterotoxin, cereolysin O, enolase) and others reduced (e.g. flagellin, L2 component of hemolysin BL, bacillolysin, sphingomyelinase, PC-PLC, PI-PLC, cytotoxin K) in the extracellular proteome of a ΔflhF mutant. Deprivation of FlhF also resulted in significant attenuation in the pathogenicity of this strain in an experimental model of infection in Galleria mellonella larvae. Our work highlights the multifunctional role of FlhF in B. cereus, being this protein involved in bacterial flagellation, swarming, protein secretion, and pathogenicity.